Bližine v skladbi near (blizu) Urške Pompe - Vrhunc, Larisa (Muzikološki zbornik, 2011)
Urška Pompe's work is a blend of diverse musical experiences, electroacoustic music not being one of them. Despite that, her music shows rather obvious influences of electroacoustics and can serve as a point of departure for consideration of the ways in which compositional techniques that stem from experiments carried out in electronic studios or with computer technology transgress the realm of pure acoustic music, as well as reflections on the history of such transgressions.
Keywords: 20./21.st.; 20th and 21st century; analiza glasbe; electroacoustic music; elektroakustična glasba; instrumental composition; instrumentalna kompozicija; music analysis; Pompe, Urška, 1969-; teorija glasbe; theory of music